Effectiveness Of Quizzizz Assessment To Improve Social Attitudes Of Elementary School Students - Nugroho, Aviandri Cahya; Sumardjoko, Bambang; Wulandari, Murfiah Dewi (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2025)
This study aims to analyze changes in students' social attitudes through the use of quizizz-based assessments. Effective learning involves not only the transfer of knowledge, but also the development of social attitudes and interaction skills. The method used is quantitative with a quasi-experimental design, namely pretest-posttest control group. The study population consisted of students in grades III-VI of SD N Pengkok 3 who were assumed to be able to operate gadgets. The sample taken by random sampling was 20 students from grade V. Data were collected through a validated social attitude questionnaire, and analyzed using a paired sample t-test after going through normality and homogeneity tests. The results of the analysis showed that the significance value of the t-test was 0.041 in the experimental group and 0.005 in the control group, which was smaller than 0.05, indicating a significant difference between social attitudes before and after using quizizz. The N Gain test showed a more significant increase in the experimental class with an average N Gain value of 0.3553 (moderate category), compared to the control class which only reached 0.1235 (low category). The results of the independent t-test showed that social attitudes in the experimental class were better than those in the control class with a significance value of 0.021. Thus, the use of quizizz-based assessments has proven effective in providing changes in students' social attitudes, strengthening interaction and collaboration among students.